Defossilising Caribbean's energy system: Highlighting on e‐fuel imports, grid integration, and accelerated transition - Ayobami S. Oyewo; Alejandro Kunkar; Dmitrii Bogdanov; Christian Breyer (IET Renewable Power Generation)
Abstract Transitioning to renewables is critical to address the Caribbean's vulnerability to imported fossil fuel price volatility and concerns about climate change. This study presents a first‐of‐its‐kind comprehensive analysis of 17 illustrative pathways varying the impact of e‐fuel imports, grid interconnections and an accelerated energy transition towards the Caribbean's carbon neutrality by 2050. The research method is based on techno‐economic principles for designing a cost‐optimal energy system. An optimisation tool is used, the LUT Energy System Transition Model, to analyse the various pathways. The study finds that high uptake of renewables in Caribbean energy systems significantly lowers costs and enhances reliability, crucial for building competitive and resilient economies. Renewable energy dominated pathways show 7–24% lower cumulative costs compared to alternatives, with grid integration reducing costs by 1–10%. Accelerated transition pathways incur 3–12% higher costs than complete defossilisation by 2050. Solar photovoltaics, wind power, batteries, and electrolysers are pivotal for achieving carbon neutrality by 2050. Importing e‐fuels reduces system costs by 7–16% and supports local resource use. Offshore renewable energy overcome land limitations, driving sustainable development and a vibrant blue economy. High electrification levels with renewable energy, sector coupling, and Power‐to‐X solutions enhance system efficiency and flexibility. Given the dominance of solar photovoltaics, the Caribbean's energy transition could be more appropriately called a ‘Solar‐to‐X Economy’. This research contributes to the international perspective on sustainable energy transition for islands.